Web Agent Event Finder (WAEF) / Masita Mohamed Shah - Mohamed Shah, Masita (2006)
The use of internet as a medium to spread information by academic organization sometimes may lead to unattained of information. Sometimes users have difficulty to access the information due the overloaded of information, thus not realizing on the information changes. Considering these problems, there is a need to routinely monitor for the information changes and retrieve the information on behalf of user. This project is aim to develop a prototype of personal agent that assist user to monitor for changes at FTMSK events webpage. In addition, the agent has the ability to notify the user whenever the changes occur. An agent called Web Agent Event Finder (WAEF) is created to retrieve and keep the information for user. In doing this function, the FTMSK events webpage was downloaded as HTML (HyperText Markup Language) document. Tag elimination process is applied to the document to remove tags and uninformative text. This process was done to extract information of the events. The agent then retrieves the webpage again based on the checking interval time that was set by the user. A comparison process is applied to identify the changes on the documents. Once the agent found the difference on the document, the agent will retrieve events information from the latest retrieval and store the information into the database. Subsequently, a message sent to user's desktop to notify the occurrence of changes to user. Process of retrieving and comparing will continue until user stop the agent's service. The WAEF prototype has demonstrated its ability to notify the changes thus reducing the unattained of information.